What weighs more—low compliance with self‐deferral or minor medical procedures? Explaining the high rate of hepatitis C virus window‐period donations in Poland. Issue 8 (28th May 2017) - Czerwinski, Michal; Grabarczyk, Piotr; Stepien, Malgorzata; Kubicka‐Russel, Dorota; Tkaczuk, Katarzyna; Brojer, Ewa; Rosinska, Magdalena
Abstract : BACKGROUND: Since the introduction of nucleic acid testing (NAT) for routine blood donor screening, hepatitis C virus (HCV) RNA‐only detection rates reported from Poland have been higher than in most other European countries. STUDY DESIGN AND METHODS: To examine factors that likely contribute to these window‐period donations, we conducted a case‐control study among 47 recently HCV‐infected blood donors (cases), who gave blood between July 2002 and June 2014, and 141 controls matched by age, sex, and donation dates. Firth‐corrected, conditional logistic regression models were fitted to estimate adjusted odds ratios and 95% confidence intervals. Adjusted population‐attributable fractions were calculated based on the distribution of exposure among the cases. RESULTS: On multivariate analysis, recent exposures in health care environments not routinely ascertained through predonation questionnaires were strongly associated with recently acquired HCV infection. These exposures included minor medical and dental procedures in the preceding 6 months (adjusted odds ratio, 5.77; 95 % confidence interval, 2.01‐18.53). However, based on the population‐attributable fraction, more important were behavioral deferrable risks that went unreported at the time of donation, such as high‐risk sexual behaviors in the preceding 6 months (population‐attributable fraction, 34%) or lifetime histories of drug use (population‐attributable fraction, 28%). CONCLUSIONS: This study raises questions about the effectiveness of deferral policy in excluding high‐risk individuals. In addition, it provides further evidence supporting short, temporal deferrals for small medical procedures and dental treatments in Poland.